Diseño de una máquina desfibradora de hojas de agave - Eredia Jiménez, Gabriel Alfredo (2024)
In the present degree work, it was proposed to design a machine for defibrated agave leaves, for which it focused on the search for information on defibrated machines for agave leaves. Likewise, information on the defibrated process and the characteristics that the agave has, paying main attention to the energy needed to break down the agave. An experimental phase was carried out to obtain the energy necessary for leaf defibrated. To determine the design to be executed, a decision matrix was made, which is made up of 4 design options, with the objective of choosing the best design option, resulting in a machine powered by a 3HP electric motor, the Defiberation is done using 12 blades, which gives a production of 10kg/h. The design of the different systems and components of the machine was based on various theories of design of machine elements. Using Autodesk Inventor Software, each part that makes up the structure of the machine was sized. Keywords: Machine, shredding defibrated, design, Agave, Inventor. Shredding machines, Agave Americana.